DISTANCE-DEPENDENT COMPETITION MEASURES IN Araucaria angustifolia, SÃO JOÃO DO TRIUNFO, STATE OF PARANA - Minatti, M.; Sanquetta, C. R.; Netto, S. P.; Corte, A. P. D. (Revista Brasileira de Engenharia de Biossistemas, 2019)
The growth behaviour of a particular species in a given region in tandem with certain environmental factors, it is possible to identify and visualise both individual and multiple tree characteristics, and to relate their productive capacity to competition, working together to facilitate decision-making in forestry intervention. This study aims to analyse and compare distance-dependent competition in individual Araucaria Angustifolia specimens in order to determine growth behaviour. Data for this study was collected from permanent plots located in São João do Triunfo, Paraná. Competition indices were evaluated using Pearson Correlation with Diameter at Breast Height (DBH) of trees sampled, model-adjusted according to the competition index. The results obtained revealed no significant difference in diameter growth between the Araucaria and Fogo plots examined. Of all the distance-dependent competition indexes assessed, Moore’s Index showed the strongest Pearson correlation (0.8831 for the Araucaria plot and 0.8560 for the Fogo plot) and also yielded the best statistical parameters.